Making Religion and Human Rights at the United Nations - Årsheim, Helge (Religion and Society, 2018)
The series Religion and Society (RS) contributes to the exploration of religions as social systems- both in Western and non-Western societies; in particular, it examines religions in their differentiation from, and intersection with, other cultural systems, such as art, economy, law and politics. Due attention is given to paradigmatic case or comparative studies that exhibit a clear theoretical orientation with the empirical and historical data of religion and such aspects of religion as ritual, the religious imagination, constructions of tradition, iconography, or media. In addition, the formation of religious communities, their construction of identity, and their relation to society and the wider public are key issues of this series.